VOMB - Johansson Liedberg, Rebecca (My University, 2025)
Ever since our first observation of the universe, outer space has been something that many of us have thought about. When refering to space, it has usually been called something underlining its depth or unknown character, e.g. “nothingness” or “way beyond”. Today, our fascination for space has spread to multiple sectors, one of them being architecture. Space exploration has brought valuable knowledge and inventions, however, not without consequences. As of today, all resources for space projects have been extracted from Earth, both financially and in terms of material. Space travel has also brought many health conerns to the human body and mind. Given this situation, the aim of this thesis was to design a visionary, functional and conceptual architectural proposal, focusing on the following questions: What can space architecture do for longterm resilience in space, both for human well-being and the human being as a species? If we want to expand in space, where would we settle first and why, from a health perspective? In order to continue with space research, we need to construct better material cycles for future space projects to come. In order to carry out longer manned space missions, more knowledge on human health needs to be applied.